Regulatory functions and pathological relevance of the MECP2 3′UTR in the central nervous system. Issue 1 (December 2015) - McGowan, Heather; Pang, Zhiping
Abstract Methyl-CpG-binding protein 2 (MeCP2), encoded by the geneMECP2, is a transcriptional regulator and chromatin-remodeling protein, which is ubiquitously expressed and plays an essential role in the development and maintenance of the central nervous system (CNS). Highly enriched in post-migratory neurons, MeCP2 is needed for neuronal maturation, including dendritic arborization and the development of synapses. Loss-of-function mutations inMECP2 cause Rett syndrome (RTT), a debilitating neurodevelopmental disorder characterized by a phase of normal development, followed by the progressive loss of milestones and cognitive disability. While a great deal has been discovered about the structure, function, and regulation of MeCP2 in the time since its discovery as the genetic cause of RTT, including its involvement in a number of RTT-related syndromes that have come to be known as MeCP2-spectrum disorders, much about this multifunctional protein remains enigmatic. One unequivocal fact that has become apparent is the importance of maintaining MeCP2 protein levels within a narrow range, the limits of which may depend upon the cell type and developmental time point. As such, MeCP2 is amenable to complex, multifactorial regulation. Here, we summarize the role of theMECP2 3' untranslated region (UTR) in the regulation of MeCP2 protein levels and how mutations in this region contribute to autism and other non-RTT neuropsychiatric disorders.